2017
DOI: 10.1016/j.bbcan.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface G-protein-coupled receptors for tumor-associated metabolites: A direct link to mitochondrial dysfunction in cancer

Abstract: Mitochondria are the sites of pyruvate oxidation, citric acid cycle, oxidative phosphorylation, ketogenesis, and fatty acid oxidation. Attenuation of mitochondrial function is one of the most significant changes that occurs in tumor cells, directly linked to oncogenesis, angiogenesis, Warburg effect, and epigenetics. In particular, three mitochondrial enzymes are inactivated in cancer: pyruvate dehydrogenase (PDH), succinate dehydrogenase (SDH), and 3-hydroxy-3-methylglutaryl CoA synthase-2 (HMGCS2). These enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 113 publications
0
51
0
1
Order By: Relevance
“…Cell cycle regulation plays an important role in cell proliferation, differentiation, and apoptosis. It has been reported that cell cycle regulation dysfunction is closely related to the development of tumors [ 38 ]. Peyressatre et al found that the deregulated activity of cyclin-dependent kinases (CDKs) contributes to altered cellular proliferation in a wide variety of human cancers [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle regulation plays an important role in cell proliferation, differentiation, and apoptosis. It has been reported that cell cycle regulation dysfunction is closely related to the development of tumors [ 38 ]. Peyressatre et al found that the deregulated activity of cyclin-dependent kinases (CDKs) contributes to altered cellular proliferation in a wide variety of human cancers [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPR81 activation occurs at a lactate concentration of 0.2-1.0 mM (119), followed by cyclic AMP downregulation and inhibition of protein kinase A (PKA)-mediated signaling (120). In the physiological context, lactate binds to GPR81, which inhibits lipolysis in fat cells (121). In the cancer context, modulation of lactate-sensing proteins, such as MCTs, ultimately leads to tumor proliferation and dissemination (122), escape from the immune system (123) and therapy resistance (124).…”
Section: Lactate As a Signaling Metabolitementioning
confidence: 99%
“…Importantly, besides the canonical role as nutrient, lactate has been shown to act as a hormone, as it is able to activate signaling pathways downstream the hydroxycarboxylic acid receptor 1, formerly known as G protein-coupled receptor 81 (GPR81). This receptor, sensitive to low concentrations of lactate (1-5 mM), is coupled to G i/q , and activation of the receptor results in decreased cellular levels of cAMP and increased cellular levels of Ca 2+ , leading a fascinating hypothesis of an autocrine and paracrine role of lactate in cancerous and stromal cell types via surface receptor (59,60). Very recently, another non-nutritional role of lactate has been reported by Zhang et al (61).…”
Section: Lactatementioning
confidence: 99%